Competência em informação na utilização do Google Classroom como ferramenta de ensino nas bibliotecas universitárias - Cavalcante, Luciano Pereira dos Santos (2024)
The librarian's role in handling information and communication technologies (ICT) nowadays has enabled the professional to develop new information skills. From this perspective, the university context represents the environment in which we witness a mass production of science, technology and information. Thus, the librarian becomes one of the important agents in the process of organizing and mediating knowledge, where one of the forms witnessed can be applied through distance training that uses digital platforms, which also includes Google Classroom. Thus, the present research aims to carry out an analysis of the information skills necessary for librarians to use Google Classroom as a teaching tool in courses offered by the Central Library of the Federal University of Ceará on the Pici Campus, based on the following guiding question: what are the essential skills in the librarian's role in using the classroom in BUs? Regarding methodological procedures, this is a field research with a qualitative approach with a descriptive and exploratory objective. In this way, an interview with fourteen questions was applied to BCCP librarians. As a data analysis technique, content analysis was used, choosing a priori the categories Information literacy and the use of technologies in the teaching process, Librarian and interaction with ICT; The librarian’s AVA pedagogical practices; Librarian's role in Google Classroom. As a result, it became evident that the librarian's competence in using Google Classroom unfolds especially in technical and political skills and in the background other skills emerge, which become essential. Thus, it is concluded that information literacy plays a crucial role in the context of university libraries, especially for the librarian when using Google Classroom as a teaching tool.